Microbial production of melanin pigments from caffeic acid and l-tyrosine using streptomyces glaucescens and fcs-ech-expressing escherichia coli - Ahn, Soo Yeon; Jang, Seyoung; Sudheer, Pamidimarri D.V.N.; Choi, Kwon Young (International Journal of Molecular Sciences, 2021)
In this study, synthetic allomelanin was prepared from wild-type Streptomyces glaucescens and recombinant Escherichia coli BL21(DE3) strains. S. glaucescens could produce 125.25 ± 6.01 mg/L of melanin with a supply of 5 mM caffeic acid within 144 h. The ABTS radical scavenging capacity of S. glaucescens melanin was determined to be approximately 7.89 mg/mL of IC50 value, which was comparable to L-tyrosine-based eumelanin. The isolated melanin was used in cotton fabric dyeing, and the effect of copper ions, laccase enzyme treatment, and the dyeing cycle on dyeing performance was investigated. Interestingly, dyeing fastness was greatly improved upon treatment with the laccase enzyme during the cotton dyeing process. Besides, the supply of C5-diamine, which was reported to lead to more complex crosslinking between melanin units, to caffeic acid-based melanin synthesis was also investigated for higher production and novel functionalities. To facilitate the supply of caffeic acid and C5-diamine, E. coli strains expressing each or combinations of tyrosine ammonia lyase/p-coumarate 3-hydroxylase, feruloyl-CoA synthetase/enoyl-CoA hydratase/al-dolase, and tyrosinase/lysine decarboxylase enzymes were prepared and investigated for their eumelanin, C5-diamine, and allomelanin production from L-tyrosine and L-lysine, respectively. Fi-nally, H-NMR, FT-IR, and MALDI-TOF analysis of the synthetic melanin pigments were attempted to obtain the chemical information.
Keywords: Antioxidants; Bacterial Proteins; Caffeic Acids; Escherichia coli; Melanins; Streptomyces; Tyrosine; Allomelanin; Caffeic acid; Eumelanin; L-lysine; L-tyrosine; Melanin-diamine complex